2014
DOI: 10.1007/s11999-014-3544-7
|View full text |Cite
|
Sign up to set email alerts
|

No Benefit of Patient-specific Instrumentation in TKA on Functional and Gait Outcomes: A Randomized Clinical Trial

Abstract: Level I, therapeutic study. See the Instructions to Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 56 publications
3
43
0
Order By: Relevance
“…Recently, Woolson et al [40] reported the results of a randomized clinical trial of 22 TKAs performed using a CT-based CCG system ( TKAs performed using standard instrumentation to assess early patient-reported and gait analysis outcomes. They found no difference in the new KSS, KOOS, SF-12, or 3-D gait parameters assessed at 3 months postoperatively between the two cohorts, but noted their results could not predict the presence of additional variances that could emerge at an intermediate followup period [1]. Thus, our study had larger cohorts with longer followup and corroborated these prior reports because no improvements in functional outcomes were seen with the use of CCGs at a mean followup of greater than 2 years.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, Woolson et al [40] reported the results of a randomized clinical trial of 22 TKAs performed using a CT-based CCG system ( TKAs performed using standard instrumentation to assess early patient-reported and gait analysis outcomes. They found no difference in the new KSS, KOOS, SF-12, or 3-D gait parameters assessed at 3 months postoperatively between the two cohorts, but noted their results could not predict the presence of additional variances that could emerge at an intermediate followup period [1]. Thus, our study had larger cohorts with longer followup and corroborated these prior reports because no improvements in functional outcomes were seen with the use of CCGs at a mean followup of greater than 2 years.…”
Section: Discussionmentioning
confidence: 93%
“…Patients were randomized to either the PSI or conventional instrumentation group by the hospital's informatics department using a previously described systematic sampling method [1]. No differences in terms of anthropometric and radiological (preoperative) parameters were found in the two groups (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…There is a paucity of published literature on the clinical outcomes after PSI surgery [7][8][9][10][11][12][13]. Furthermore, these studies are also limited by their short follow-up periods.…”
mentioning
confidence: 99%